2022
DOI: 10.1002/path.6040
|View full text |Cite
|
Sign up to set email alerts
|

EBV infection mediated BDNF expression is associated with bladder inflammation in interstitial cystitis/bladder pain syndrome with Hunner's lesion

Abstract: Interstitial cystitis/bladder pain syndrome with Hunner's lesion (HIC) is characterized by chronic inflammation and nerve hyperplasia; however, the pathogenesis of HIC remains a mystery. In this study, we detected both Epstein–Barr virus (EBV) latency infection genes EBNA‐1 and LMP‐1 and EBV lytic infection BZLF‐1 and BRLF‐1 expression in the HIC bladders, indicating the coexistence of EBV persistence and reactivation in the B cells in HIC bladders. Upregulation of EBV‐associated inflammatory genes in HIC blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…31 Jhang et al found that BDNF alteration in Epstein-Barr virus-infected B cells inhibits cell proliferation and viability in IC/BPS models. 32 Akiyama et al found defective umbrella cells with urothelial denudation, integrity defects, and pleomorphism in animal model with autoimmune cystitis. 29 These electron microscopic findings were also observed in human bladders and correlated with symptom severity in patients with HIC and NHIC.…”
Section: Pathophysiology and Multidisciplinary Approach Of Ic/bpsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Jhang et al found that BDNF alteration in Epstein-Barr virus-infected B cells inhibits cell proliferation and viability in IC/BPS models. 32 Akiyama et al found defective umbrella cells with urothelial denudation, integrity defects, and pleomorphism in animal model with autoimmune cystitis. 29 These electron microscopic findings were also observed in human bladders and correlated with symptom severity in patients with HIC and NHIC.…”
Section: Pathophysiology and Multidisciplinary Approach Of Ic/bpsmentioning
confidence: 99%
“…Brain‐derived neurotrophic factor (BDNF) deficiency may cause dysregulated neuroinflammatory and metabolic responses 31 . Jhang et al found that BDNF alteration in Epstein–Barr virus‐infected B cells inhibits cell proliferation and viability in IC/BPS models 32 . Akiyama et al found defective umbrella cells with urothelial denudation, integrity defects, and pleomorphism in animal model with autoimmune cystitis 29 .…”
Section: Pathophysiology and Multidisciplinary Approach Of Ic/bpsmentioning
confidence: 99%
“…We used in situ hybridization and PCR to assess the presence of EBV, and EBV infection was identified in the bladder specimens of 87.5% and 17.4% of patients with HIC and NHIC, respectively [ 8 ]. In a subsequent study, we reported that both latent and lytic EBV infection were present in the bladders of patients with IC/BPS [ 9 ], suggesting EBV reactivation in the bladders. We also provided molecular evidence demonstrating that EBV infection is associated with the upregulation of brain-derived neurotrophic factor and EBV-associated inflammatory cytokines in the bladders of patients with IC/BPS [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent study, we reported that both latent and lytic EBV infection were present in the bladders of patients with IC/BPS [ 9 ], suggesting EBV reactivation in the bladders. We also provided molecular evidence demonstrating that EBV infection is associated with the upregulation of brain-derived neurotrophic factor and EBV-associated inflammatory cytokines in the bladders of patients with IC/BPS [ 9 ]. Therefore, infection with EBV may be an etiology in some patients with IC/BPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation